Molecular characterization of virulence genes in vancomycin-resistant and vancomycin-sensitive enterococci - Priyanka Paul Biswas; Sangeeta Dey; Aninda Sen; Luna Adhikari (Journal of Global Infectious Diseases, 2016)
Background: The aim of this study was to find out the correlation between presence of virulence (gelatinase [gel E], enterococcal surface protein [esp], cytolysin A [cyl A], hyaluronidase [hyl], and aggregation substance [asa1]) and vancomycin-resistant genes (van A and van B) in enterococci, with their phenotypic expression. Materials and Methods: A total of 500 isolates (250 each clinical and fecal) were processed. Enterococci were isolated from various clinical samples and from fecal specimens of colonized patients. Various virulence determinants namely asa1, esp, hyl, gel E, and cyl were detected by phenotypic methods. Minimum inhibitory concentration (MIC) of vancomycin was determined by agar dilution method. Multiplex polymerase chain reaction (PCR) was used to detect the presence of virulence and van genes. Results: Out of all the samples processed, 12.0% (60/500) isolates carried van A or van B genes as confirmed by MIC test and PCR methods. Genes responsible for virulence were detected by multiplex PCR and at least one of the five was detected in all the clinical vancomycin-resistant enterococci (VRE) and vancomycin-sensitive enterococci (VSE). gel E, esp, and hyl genes were found to be significantly higher in clinical VRE. Of the fecal isolates, presence of gel E, esp, and asa1 was significantly higher in VRE as compared to VSE. The presence of hyl gene in the clinical VRE was found to be statistically significant (P = 0.043) as against the fecal VRE. Correlation between the presence of virulence genes and their expression as detected by phenotypic tests showed that while biofilm production was seen in 61.1% (22/36) of clinical VRE, the corresponding genes, i.e., asa1 and esp were detected in 30.5% (11/36) and 27.8% (10/36) of strains only. Conclusion: Enterococcus faecium isolates were found to carry esp gene, a phenomenon that has been described previously only for Enterococcus faecalis, but we were unable to correlate the presence of esp with their capacity to form biofilms.